2005
DOI: 10.1086/431484
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Determinants, and Clinical Relevance of CD4 T Cell Recovery to <500 Cells/ L in HIV Type 1--Infected Individuals Receiving Potent Antiretroviral Therapy

Abstract: Background. The CD4 T cell count recovery in human immunodeficiency virus type 1 (HIV-1)-infected individuals receiving potent antiretroviral therapy (ART) shows high variability. We studied the determinants and the clinical relevance of incomplete CD4 T cell restoration.Methods. Longitudinal CD4 T cell count was analyzed in 293 participants of the Swiss HIV Cohort Study who had had a plasma HIV-1 RNA load !1000 copies/mL for у5 years. CD4 T cell recovery was stratified by CD4 T cell count 5 years after initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
273
5
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(320 citation statements)
references
References 30 publications
30
273
5
12
Order By: Relevance
“…1,59 We found that the identical clinical parameters were associated with increased rate of CD4 T-cell recovery by using both approaches and were consistent with other observational studies of CD4 T-cell recovery after cART. 2,16 It is important to note however, that this study was designed to replicate our previous study of Caucasians 22 where we had previously used a survival analysis approach. However, in this study of the UARTO patients, there was a much lower frequency of patients achieving the event (that is, CD4 T-cells 4500cells ml À1 ) as compared with the Caucasians in our prior study 22 (15 versus 80% respectively) and this may have led to over-fitting of the Cox model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,59 We found that the identical clinical parameters were associated with increased rate of CD4 T-cell recovery by using both approaches and were consistent with other observational studies of CD4 T-cell recovery after cART. 2,16 It is important to note however, that this study was designed to replicate our previous study of Caucasians 22 where we had previously used a survival analysis approach. However, in this study of the UARTO patients, there was a much lower frequency of patients achieving the event (that is, CD4 T-cells 4500cells ml À1 ) as compared with the Caucasians in our prior study 22 (15 versus 80% respectively) and this may have led to over-fitting of the Cox model.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] These patients remain at increased risk of non-AIDS-related illnesses and mortality despite years of suppressive cART. [4][5][6] Clinical or genetic factors that may predict impaired CD4 T-cell recovery could potentially be used to identify patients who would benefit from earlier initiation of cART.…”
Section: Introductionmentioning
confidence: 99%
“…[78][79][80][81][82][83] Some suggests that these finding may be linked with higher adherence in older patients, 78,[84][85] but other authors reported a higher risk of inadequate adherence in HIV patients who have other comorbidities and take other medications besides HAART. [86][87] While virological response seems not to be influenced by age, at least biologically, older patients have lower CD4C T-cell gain compared with younger persons, [88][89][90][91][92][93][94][95] even when adjusted for antiretroviral therapy regimens. This is particularly relevant considering that lower CD4 T-cell counts are not only linked to HIV-related opportunistic infections and malignancies, but also lead to higher risk of non-AIDS-related comorbidities, adding to the already elevated risk conferred by age.…”
Section: Clinical Outcomementioning
confidence: 99%
“…High plasma HIV-RNA levels and low CD4+ cell counts, typically found in advanced stages of HIV disease, are both associated with an increased risk of mortality, even after the initiation of combination antiretroviral therapy (cART) [4,5]. In addition, even after cART has been initiated, early viro-immunologic response may be incomplete or slower in patients with more advanced HIV infection at baseline [6,7], and it is also strongly associated with subsequent disease progression [8].…”
Section: Introductionmentioning
confidence: 99%